Thin, muscular, and fit-ideals: Prevalence and correlates in undergraduate women. Issue 8 (17th November 2022) - Wagner, Allison F.; Bennett, Brooke L.; Stefano, Emily C.; Latner, Janet D.
Abstract: Objective: The current study aimed to compare endorsement of the muscular- and thin-ideals alone, as well as simultaneous endorsement of both as representative of the fit-ideal and examine potential negative correlates of each type of ideal internalization. Participants: Participants were 300 female undergraduate students. Methods: Participants completed measures of internalization of the thin- and muscular-ideals, body dissatisfaction, body checking, and body avoidance. Results: Analyses revealed that approximately 24.9% of participants endorsed scores in the upper quartile on thin-ideal internalization, and 27.4% of participants fell in the upper quartile of muscular-ideal internalization, while 10.3% endorsed high internalization of both ideals. Analyses revealed that individuals endorsing only the thin-ideal reported significantly higher levels of body dissatisfaction and body avoidance than those endorsing the fit-ideal. Conclusions: Overall, findings suggested that thin- and muscular-ideal internalization present different patterns of association depending on whether an individual endorses one or both of these body ideals.